(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article highlights the legal foundations for combating the entry of narcotic drugs and psychotropic substances into the territory of Uzbekistan, which pose a threat and concern to the international community. It also analyzes, with scientific examples, the illegal trafficking and distribution of these substances within the country, along with their negative consequences. Furthermore, the article sheds light on the tragic fate of individuals, especially young people, who fall victim to these narcotic substances in the Central Asian region, and emphasizes the role of spirituality in the fight against them.